(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2020)
A software quality is defined based on the analysis of the study of external and internal features of the software. The external quality is defined based on how software performs in real time scenario in operational mode and how useful it is for its end users. The internal quality focuses on the essential aspects that are dependent on the quality of the code written by coder. The main aim of this literature paper is to study the measures available to decide different quality assurance. The detection of quality software assurance as well as themetrics and measures will be done on the basis of the literature survey by studying and analysis various research papers. From this literature paper the researchers, academicians and software developer can easily detect the metrics to measure the quality software characteristics of the same. In addition, the work focused at providing more suggestions.